Study of drug utilization pattern in the department of obstetrics and gynecology - Dr.Jayashree A K3Perasani Umarani*1, Fereshteh Makiabadi1, Rajeswari.K2 (Journal of Biomedical and Pharmaceutical Research, 2017)
Objective: To assess the drug utilization pattern of drugs in the department of obstetrics and gynecology at tertiary care Hospital. Materials and Methods: A prospective observational study on drug utilization pattern was done in the department of obstetrics and gynecology of a 950 bedded tertiary care teaching hospital in Bangalore for a period of 6 months. Patients satisfying inclusion criteria were enrolled after obtaining Informed consent. Patient’s data entered into case report form (CRF). Medication orders were observed for drug utilization Pattern. WHO prescription indicators was used to study the prescription pattern. Results: A total of 120 cases were enrolled. A total of 1004 drugs were prescribed which included 244 (24.30%) minerals and vitamin supplements, 219 (21.81%) antibiotics, 146 (14.55%) gastric acid secretion inhibitors, 108 (10.75% ) analgesics, 35 (3.49%) antihypertensive drugs, 22 (2.19%) antifungal drugs, 32 (3.19%) anti diabetic drugs, 32 (3.19%) antispasmodics, 41 (4.08%) antiemetic drugs, 12 (1.19%) corticosteroids, 16 (1.59%) anticonvulsant drugs, 97 (9.66%) in the category of others: antiseptics, topical agents, oxytocic, antihyperlipidemic drugs, oral contraceptives etc. Average number of drugs per encounter 8.36, Drugs prescribed by generic name 17.03%, antibiotics prescribed per encounter 21.81%, number of injections per encounter 39.74%, number of drugs from essential drug medicine list 79.08%. Conclusion: Minerals and vitamin supplements are the most frequently prescribed drugs. Overall drug use pattern is rational with few exceptions like polypharmacy. Majority of drugs were prescribed as per FDA category A the safest Category during pregnancy. This type of study can help in evaluating the existing drug use pattern and in planning appropriate interventions to ensure rational drug therapy. Keywords: Prescription pattern, Rational Drug use , Obstetrics and Gynecology